Advances in brain-heart syndrome: Attention to cardiac complications after ischemic stroke - Wang, Min; Peng, Ya (Frontiers in Molecular Neuroscience, 2022)
Neurocardiology is an emerging field that studies the interaction between the brain and the heart, namely the effects of heart injury on the brain and the effects of brain damage on the heart. Acute ischemic stroke has long been known to induce heart damage. Most post-stroke deaths are attributed to nerve damage, and cardiac complications are the second leading cause of death after stroke. In clinical practice, the proper interpretation and optimal treatment for the patients with heart injury complicated by acute ischemic stroke, recently described as stroke-heart syndrome (SHS), are still unclear. Here, we review the recent research progress of SHS to provide a theoretical basis for future research and clinical decision-making.